PERANCANGAN SISTEM INFORMASI TRACER STUDY PADA UNIVERSITAS BANTEN JAYA - Sutanto Sutanto; Widyawati Widyawati; Firhan Adnan Denoor (Program Studi Sistem Informasi, Universitas Banten Jaya, 2020)
Banten Jaya University is a tertiary institution located in Serang City, Banten Province. Which has three faculties including education, computer science and engineering. In a university, information about alumni data is needed, starting from the department, graduation year, place of work and other information related to the alumni. Tracer Study is useful as a link between universities and the business world and industry. The tracer study process at Banten Jaya University is still not optimal, because the data collection is still done manually by distributing questionnaires to alumni and lack of information dissemination to alumni, because it is limited only through social media. This is why the information system Tracer Study is built using the PHP programming language and MySQLi as the database, to collect alumni information. This information system uses web-based technology and the waterfall method in the development. From the results of testing this system is in accordance with the algorithm that was made,users can fill out questionnaires online, see other alumni information, and managing job openings, as well as displaying graphs of alumni who had worked after graduation and the number of graduates each year.